LAW AND POLITICAL CORRUPTION BY PARTY CORPORATIONS IN INDONESIA - Bambang Yugo Pamungkas; Eko Wahyudi (RADJA PUBLIKA, 2025)
This research aims to examine corruption crimes committed by political parties. This article discusses (1) corruption crimes committed by political parties as corporations; (2) law enforcement against corporate political parties that commit acts of corruption; and (3) the ideal concept of law enforcement on corporate corruption crimes of political parties from the perspective of prophetic law in Indonesia. The research method used is empirical legal research based on case studies. Data collection techniques were carried out through interviews, observation, field notes, and library research. Data analysis used qualitative descriptive analysis techniques and juridical analysis. The results of the study show that (1) Corruption crimes committed by political parties as corporations can be prosecuted based on four basic justifications. Even though, until now there have been no sanctions against political parties against criminal acts committed by members of political parties even though they actually fulfill the elements of criminal acts of corruption; (2) There are several types of law enforcement against corporate political parties that commit acts of corruption. If you use the provisions in Article 20 of the Corruption Law jo. Amended Corruption Law, the form of sanction against political parties is only a fine with a maximum penalty plus 1/3 (one third). However, if you use the provisions in Article 7 of the TPPU Law, the form of sanctions can be in the form of fines; announcement of the judge's decision; suspension of part or all of political party business activities; revocation of political party operational permits; dissolution and/or banning of political parties; confiscation of political party assets for the state, and/or taking political parties by the state; and (3) The ideal concept of law enforcement for political party corporate corruption crimes from the perspective of prophetic law in Indonesia is based on a comparative study between the United States criminal law system and the Dutch criminal law system regarding the concept of corporate/organizational punishment. In addition, it also promotes prophetic values ​​for the prevention of corruption.